SOSIALISASI ALAT PELINDUNG DIRI SEBAGAI UPAYA MENJAGA KESELAMATAN DAN KESEHATAN KERJA KEPADA PEKERJA (LOKASI: PEMBANGUNAN EMBUNG BANDARA BUNGO, KABUPATEN BUNGO, PROVINSI JAMBI) - Radinal; Doli Jumat Rianto; Sucitra Wijaya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
In the Muara Bungo Airport area, Jambi Province, there is a valley surrounded by hilly areas that have quite dense vegetation. Some of the morphology in the reservoir area is relatively lower than the surrounding area, so it is inevitable that there will be water flow in the airport area. This arises because of the process of collecting groundwater flow that flows from higher places (hills) to lower places (valleys). This condition continues both in the dry season and in the rainy season. In the rainy season the flow of water will be greater due to additional surface water (run off) from rainwater. This condition is evidenced by the constant flow of surface water in the form of rivers flowing in the airport area. With the current conditions, a Embung construction is needed that can anticipate flooding in the Muara Bungo Airport area. Based on the results of the socialization obtained (1) participants can recognize the types and specifications of the Personal Protective Equipment (PPE) used in accordance with the hazard factors in the workplace. (2) participants can explain the physical feasibility and function of Personal Protective Equipment (PPE) and inappropriate PPE conditions in the workplace. (3) participants are accustomed to using PPE and always pay attention to the PPE used by service use and in accordance with workplace conditions